2012
DOI: 10.1007/s10238-012-0215-4
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein 2A genetic polymorphisms and risk of ductal breast cancer

Abstract: Metallothioneins (MTs) are a family of metal binding proteins that play an important role in cellular processes such as proliferation and apoptosis. Metallothionein 2A is the most expressed MT isoform in the breast cells. A number of studies have demonstrated increased MT2A expression in various human tumors, including breast cancer. We carried out an association study to examine whether MT2A gene polymorphisms are associated with risk of breast cancer. Information on lifestyle risk factors was collected via a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 26 publications
(36 reference statements)
1
53
0
2
Order By: Relevance
“…The literature provides numerous studies investigating the toxic and tumorigenic potential of metallic agents, heavy metals and their compounds in cancerous diseases, which confirm their association with progression of neoplastic processes (Ahamed and Alhadlaq, 2014; Krześlak Unfortunately, despite much research on the contribution of MT2A isoforms to tumorigenesis and behavior of various human cancers as well as patient prognosis, a literature review often demonstrates contradictory results and ambiguous conclusions (Forma et al, 2012;Kita et al, 2006;Krześlak et al, 2014Krześlak et al, , 2013Mehus et al, 2014;Pedersen et al, 2009). Most studies introduce some evidence for an association of increased MT1/MT2 isoform expression in neoplastic lesions with such clinicopathological parameters as higher stage and local tumor extension, lower grade and increased patient mortality.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The literature provides numerous studies investigating the toxic and tumorigenic potential of metallic agents, heavy metals and their compounds in cancerous diseases, which confirm their association with progression of neoplastic processes (Ahamed and Alhadlaq, 2014; Krześlak Unfortunately, despite much research on the contribution of MT2A isoforms to tumorigenesis and behavior of various human cancers as well as patient prognosis, a literature review often demonstrates contradictory results and ambiguous conclusions (Forma et al, 2012;Kita et al, 2006;Krześlak et al, 2014Krześlak et al, , 2013Mehus et al, 2014;Pedersen et al, 2009). Most studies introduce some evidence for an association of increased MT1/MT2 isoform expression in neoplastic lesions with such clinicopathological parameters as higher stage and local tumor extension, lower grade and increased patient mortality.…”
Section: Discussionmentioning
confidence: 94%
“…The importance of the relationship between MT2A SNP and aberrant expression of heavy and toxic metals in malignant or benign tumors has been investigated in only a few studies and the relationship itself remains largely unknown. Studies on various types of tumors indicate that rs28366003 plays an important role in the determination of the levels of metals such as Cd, Zn and Pb, but divergent results concerning − 5 A/G MT2A and metal toxicity can be found (Kayaalti et al, 2010(Kayaalti et al, , 2011Krześlak et al, 2014;Seibold et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Using this method Krześlak et al investigated three known single nucleotide polymorphisms (SNP) of MT2A gene in patients with breast cancer [39]. They found that the rs28366003 SNP of MT2A is positively associated with breast cancer.…”
Section: Pcr and Rt-pcrmentioning
confidence: 99%
“…MTs are overexpressed in several tumors and this overexpression is accompanied by an increased proliferation and protection against apoptosis. Therefore, MTs can be considered as a sign of worse prognosis in some malignancies [12][13][14][15]. Some previous studies showed that the MT level correlates inversely with tumor grade [16], which led us to consider the MTs as a potential cancer marker [6,7,17].…”
Section: Introductionmentioning
confidence: 99%